식물명 상기생(桑寄生)의 분류학적 실체 - 신현철; Hyunchur Shin; 정종덕; Jongduk Jung (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2018)
『향약채취월령』과『동의보감』을 비롯한 우리나라 옛 문헌에 나오는 식물명 상기생(桑寄生)은 지금까지 뽕나무겨우살이(Loranthus parasiticus), 꼬리겨우살이(Loranthus tanakae), 참나무겨우살이(Taxillus yadoriki), 뽕나무겨우살이(Taxillus chinensis), 동백나무겨우살이(Korthalsella japonica), 그리고 겨우살이(Viscum album var. coloratum)로 알려져 왔다. 최근에는 상기생(桑寄生)이 국내에는 분포하지 않는다는 주장도 제기되었으나, 옛 문헌에 기록된 상기생은 중국에서 부르는 상기생, 즉 Taxillus sutchuenensis과는 다른 겨우살이(V. album var. coloratum)임이 확인되었다. 상기생을 뽕나무겨우살이라고 불렀으나, 최근에는 겨우살이로 부르고 있음이 확인되었다. References in the modern Korean literature in this area to the Korean medicinal plant name written in Chinese script and expressed as Sanggisaeng have been extremely confusing. This name has been considered as six species, specifically Loranthus parasiticus, Loranthus tanakae, Taxillus yadoriki, Taxillus chinensis, Korthalsella japonica, and Viscum album var. coloratum. Recently, it was suggested that sanggisaeng is not distributed in Korea; however, the plant name Sanggisaeng recorded in old Korean literature sources, such as in the Hyang-yak-chaechwi- wol-lyeong, Hyang-yak-jib-seong-bang, and Dong-ui-bo-gam sources, among others, was identified using the name V. album var. coloratum, whereas in China, Sanggisaeng was referred to as T. sutchuenensis. The Hangeul name of Sanggisaeng had been Ppongnamugyeousali, but now the name Gyeousali is widely used.